The tenacity of the couple-norm : intimate citizenship regimes in a changing Europe /: intimate citizenship regimes in a changing Europe. (2020) - Roseneil, Sasha, 1966-; Crowhurst, Isabel; Hellesund, Tone; Santos, Ana Cristina; Stoilova, Mariya
No abstract available